CHEMICAL COMPOUND FEATURIES OF TI-BEARING GABBROIDS OF KOROSTEN PLUTONE - Mitrokhina, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The chemical compound of Ti-bearing gabbroids from Kropivnja, Penizevichy, Fedorivka and Stremigorod intrusions (Korosten pluton) is studied. It is found out that geochemical features of the studied magmatic rocks reflect quantitative parities and a chemical compound of rock-forming minerals which in turn are defined by primary composition of parent magmas and also by the subsequent processes of magmatic evolution. Low-temperature postmagmatic processes haven’t affected on redistribution of TiO2 and FeO in Tibearing gabbroids. The author assumes that parent magmas for Ti-bearing olivine gabbro intrusions were subalkaline olivine ferrobasalt initially enriched by Ti and P. The chemical compound of studied Ti-bearing rocks is average-weighted from cumulate minerals precipitated by crystal-sorting and gravitation-kinetic processes and also from the interstitial melt trapped during the crystallization.